Epidemiological and clinical characteristics of myasthenia in the Krasnoyarsk region - E. D. Gasymly; N. V. Isaeva; S. V. Prokopenko; Yu. N. Andon (Нервно-мышечные болезни)
Aim. To study the epidemiological features of myasthenia gravis in the Krasnoyarsk region.Materials and methods. 314 cases of myasthenia gravis, registered by the Krasnoyarsk regional health information analytical center, 87 of these patients were under constant monitoring.Results. Mean age of the patients was 45.4 (SD 4.5) years. The number of women in the observed group – 66 (75.86 %), which was 3 times more than men – 21 (24.14 %). The prevalence was 10.98 per 100.000 population, the primary incidence – 0.01 by 1000.Conclusion. Clinical features of the disease in the region were established, the register of patients with myasthenia was formed. From September 2016 a department of the neuromuscular pathology on the basis of advice Regional Hospital was formed.